1983
DOI: 10.1203/00006450-198301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Respiratory Instability in Term Neonates under Hyperthermic Conditions: Age, Sex, Type of Feeding, and Rapid Eye Movements

Abstract: SummaryThe purpose of this study was to examine the influence of neonatal age, sex, type of feeding, and rapid eye movements on the occurrence of apneic pauses during sleep in a hyperthermic environment. One hundred and twenty fullterm infants (equally divided by sex and type of feeding) were observed during a complete nap within the first and approximately fourth wk of life. Each sleep session was characterized by twenty-one measures including the longest apneic pause, mean apnea duration, relative frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
(15 reference statements)
0
4
1
Order By: Relevance
“…The observation in the current study that slower breathing frequency in preterm and former preterm infants is associated with REM sleep conflicts with previous studies [10,15]. Steinschneider and Weinstein [14] reported similar findings and suggested that differences in environmental conditions (room temperature) could be responsible. Room temperature was not measured during our investigations.…”
Section: Discussioncontrasting
confidence: 50%
“…The observation in the current study that slower breathing frequency in preterm and former preterm infants is associated with REM sleep conflicts with previous studies [10,15]. Steinschneider and Weinstein [14] reported similar findings and suggested that differences in environmental conditions (room temperature) could be responsible. Room temperature was not measured during our investigations.…”
Section: Discussioncontrasting
confidence: 50%
“…In many studies a relationship has been found between the incidence of apnoeic spells and the behavioural state of the infant (8)(9)(10). It has been suggested that a better description of the behavioural state of these infants can contribute to the identification of infants at risk for SID.…”
mentioning
confidence: 99%
“…A rapid increase in incubator air temperature and hyperthermia have been associated with respiratory instability. 24,25 Sleep is essential for normal infant growth and development, and infant body temperature biorhythm and sleep-wake pattern are closely related. 26 The effects of incubator operation mode may be reflected in an altered sleep-wake pattern.…”
Section: Summationmentioning
confidence: 99%